Repenser Le Rôle Des Institutions De Conservation De La Nature À L’ère De La Globalisation En Afrique: À Propos Du Parc National De La Salonga (RDC) - Salomon, Mampeta Wabasa (European Scientific Journal, ESJ, 2017)
In the Democratic Republic of the Congo (DRC), the protectionist conservatism influenced by colonialism, which exploited African countries for the prosperity of the colonizing countries, still has a high visibility in the Salonga National Park (PNS). If, in theory, the Central Africans seem to free themselves from the colonial powers on their land, in practice they are still there. The hostility of settlers who have become neo-colonists to the development of Central Africa remains intact, he adds (Ndinga, 2003). This reflects a "logic from above" that has disregarded local values. Yet, in the era of sustainable development and globalization, African protected areas appear to be essential tools for States to reposition themselves in a complex set of actors with the aim of capturing and using the new environmental rent (Giraut, Guyot, & Houssay-Holzschuch, 2003). This is a "bottom-up logic", placing people at the heart of all activities and aiming to reorganize their long-term relationships with the environment. From these two logics, a third "logic from the other side" emerges, reflecting a collective awareness of the fragility of the planet. The restoration of the rights of Africans in the various national frameworks constitutes a major challenge for the contemporary management of African protected areas. Because the protected areas inherited from the different colonial systems must accompany the change in management methods and the redefinition of their functions in order to better serve the local community in the long-term.